THE ROLE OF VIRTUAL SPORTS PRODUCTS IN ENHANCING THE COMPETITIVENESS OF SPORTS ORGANIZATIONS: ANALYSIS OF STRATEGIES AND OPPORTUNITIES (TRAKIA JOURNAL OF SCIENCES, 2025)
Sports organizations face the challenge of maintaining or increasing their competitive advantage in the digital era, where consumers increasingly turn to virtual and online experiences. Establishing a strong business presence in this context requires adaptation and innovation, including the use of virtual sports products to attract and engage customers. Integrating such products into the strategies and plans of sports organizations presents an exciting opportunity for innovation and adaptation to the rapidly evolving market. By leveraging these products, sports organizations can enhance their services, attract new customers, and stand out in an increasingly competitive environment.The scope of this study includes analyzing strategies and opportunities for integrating virtual sports products into the product policy of a sports organization. The research tasks are related to:Study of the theoretical and methodological foundations for the development of virtual sports products as a new tool in the product policy of sports organizations.Research, analysis, and justification of models for implementing virtual sports products as a means to enhance the competitive advantage of production structures.Analysis of the promotional policy used to promote virtual sports products in marketing practice.The results of the study include an assessment of the impact of digital services on the activities of sports clubs, as well as an analysis of an adapted model applied in the sports sector.